Political Culture of the Political Elite in Libya: A Study of Political Preparation Programmes of the Secretariat of the BC and Secretariat of the PC - العبيدي أمال (Dirasat in Economics and Business, 2006)
The key concern of this paper is to explore the political culture of the politically relevant elite, represented in this study through the Secretariat of the Basic Congresses and Secretariat of the People's Committees at the local level, as an access to popular opinion and a source of the regime's legitimacy. One can expected that these two particular groups are powerful and have influence more than any other groups within the elite structure. However, in reality, these two groups do not constitute a major policy channel. They have no power although their role lay on projecting the regime's legitimacy, as these congresses and committees are projected as the corner stone of the political structure of the political system. attention will be paid to the political preparation programmes. In exploring the attitudes of the participants of these programmes, the study depend on a focus groups method. This was done through focusing on two groups of a random sample of the Secretariat of the Basic Congresses and Secretariat of the People's Committees. The issues discussed among these two groups were: the ability to influence the decision taken in the political process, the nature of the Secretariat of the Basic Congresses and Secretariat of the People's Committees role and duties, the political preparation programmes, the role of the tribe and finally, the role of women in the Libyan society. This paper will pay attention to the role of the main political socialisation agents used by the political system in Libya ; special